Nanotechnology for Environmental and Biomedical Research - Frenzilli, Giada (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Do you care about your environment and your health? Contamination by hazardous substances in environmental matrices, including landfills, oil fields, and manufacturing and industrial sites, represents a global concern and needs to be remediated since it poses a serious risk to the environment and human health. Particular attention should also be paid to the use of medical devices and recent developments in the use of nanoparticles expressed as drug delivery systems designed to treat a wide variety of diseases. This Special Issue collects a compilation of articles that strongly demonstrate the continuous efforts made in developing advanced and safe nanomaterial-based technologies for nano-remediation and for drug delivery and other biomedical applications. It covers the most recent advances in the safe nanomaterials synthesis field as well as in environmental applications, in the use of restorative materials, drug delivery and other clinical applications, in order to lay the foundations for a cleaner and healthier future.